Toward the Development of Personalized Syndrome Discriminant Systems: A Discriminant System for Hypertension with Liver Yang Hyperactivity Syndrome - Guang-yao Shang (Hindawi Limited, 2021)
Traditional Chinese medicine has shown promising results in treating the symptoms of hypertension, a major global health concern not yet fully managed by modern medicine. It is, therefore, of high priority to clarify the altered pathophysiology of hypertension in individuals with liver Yang hyperactivity syndrome (HLYH) in response to effective treatments to better understand this disorder. The primary aim of this study was to construct a personalized syndrome discriminant system based on data capable of informing management strategies prior to the initiation of antihypertensive therapy or the implementation of screening strategies in at-risk HLYH. Based on the successful replication of HLYH rat models, we extracted the core discriminant factors of the disorder through the integration of physical signs, biochemical indicators, and metabolic markers. Macro and micro information was correlated to construct a syndrome discriminant system. At the macroscopic level, HLYH rat models characterized by elevated blood pressure were found to be associated with significant changes in water intake, pain threshold, retention time on a rotating platform, and body surface temperature. A total of 27 potential biomarkers and 14 metabolic pathways appeared to reflect the primary metabolic characteristics. Through the integration of these data, we successfully constructed a combined macro-micro personalized syndrome discriminant system, which provides a foundation for research regarding the risk loci of HLYH. Our findings also broaden our understanding of the biological pathways involved in HLYH.